Influence of high-flux hemodialysis on micro-inflammatory and malnutrition state in patients with uremia - SHEN Wei; YANG Ting (Linchuang shenzangbing zazhi)
Objective To explore the influence of high-flux hemodialysis(HFHD)on micro-inflammatory and malnutrition state in patients with uremia.Methods The selected 70 cases of uremia from October 2012 to December 2014 in our hospital were randomly divided into control group and improvement group(n=35 each).The patients in control group were treated by conventional hemodialysis,and those in improvement group were treated by HFHD for 6 months.Hemoglobin B(Hb),serum total protein(TP),albumin(Alb),transferrin(TRF),the levels of malnutrition inflammation score(MIS),high sensitivity C reactive protein(hs-CRP),tumor necrosis factor-α(TNF-α)and interleukin-6(IL-6)were detected before and 6 months after therapy.Changes in the parameters for micro-inflammatory and malnutrition state were observed before and after the treatments in the two groups.Results There was no statistically significant difference between two groups before therapy(P>0.05).After therapy,the levels of MIS,hs-CRP,TNF-αand IL-6 were significantly lower,and levels of Hb,TP,Alb and TRF were significantly higher in the improvement group,and there was significant difference between the improvement group and the control group(P<0.05).ConclusionsThe levels of serum CRP,IL-6 and TNF-αincrease significantly in uremic patients,suggesting the existence of micro-inflammatory state in hemodialysis patients.HFHD can effectively decrease the levels of serum hsCRP,TNF-αand IL-6,and improve the micro-inflammatory and malnutrition state in patients with uremia.